(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This aim of this paper is to examine the role of transformational leadership and organizational change in driving digital transformation in business sector. In the context of digital transformation, the paper argues that transformational leadership is more effective and efficient than transactional leadership. Previous studies have not noted the significance of transformational leadership in using digital transformation. To deal with this gap, this paper takes a case study of DEOCA Group, Vietnam’s largest transportation infrastructure company. The findings shows that digital transformation puts pressure on leaders, managers, and personnel to adapt to digital communications, modifications in data and information, and new collaboration and creativity skills. The paper unearths out that achieving a faster pace of digital transformation calls for fostering organizational culture exchange and introducing transformational leadership at all levels of the management system, not just the top management. The study suggests that the DEOCA group should change its recruitment, promotion, and training policies to enhance transformational leadership qualities across the organization. The findings therefore provide valuable insights and recommendations for other prominent companies in Vietnam undergoing similar organizational culture and leadership transformations in the face of digital transformation challenges.